Biopriming with Trichoderma spp. as a Strategy to Enhance Seed Viability and Vigor in Several Rice Varieties (Oryza sativa L.) - Due, Maria Serviana; Djawapatty, David Januarius; Nosen, Ludgardis Keas; Bay, Jenny Ronawati; Bao, Antonia Paulina; Limbu, Nataniel Umbu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Rice plants frequently encounter both biotic and abiotic stress because the nation is tropical. Through the application of ecologically friendly technology, the sustainability of diminishing rice production can be addressed. Trichoderma spp. microorganisms used in biopriming may be able to address the issues that come up. The purpose of the research is to determine how bio priming using Trichoderma spp. affects the viability and vigor of seeds from several rice varieties. (Oryza sativa L.). This study employs an experimental approach with a Completely Randomized approach (CRD) factorial design that includes two factors: the rice variety and the concentration of Trichoderma spp. Two-way analysis of variance (ANOVA) was used to analyze the data. The findings of the study show that seed vigor and viability are significantly impacted by biopriming with Trichoderma spp. For the Kusuma 05 rice variety, the treatment with Trichoderma spp. at a 30% concentration showed the largest increase in each variable.